A comprehensive analysis of the effects of risk measures on bank efficiency: Evidence from emerging Asian countries - Sun, Lei; Chang, Tzu-Pu (Journal of Banking & Finance, 2011)
This study investigates the role of risk in determining the cost efficiency of international banks in eight emerging Asian countries. Researchers of this paper consider three distinct risk aspects under a total of eight risk measures: credit risk, operational risk, and market risk. We apply a heteroscedastic stochastic frontier model to estimate bank cost efficiency in our analysis. Additionally, this study analyzes the marginal effects of all risk measures on the inefficiency effect in order to explore a more detailed relationship between risks and efficiency. The empirical results indicate that the risk measures represent significant effects on both the level and variability of bank efficiency. We also find that these effects vary across countries and over time.